Proteinaceous plug and urethral ectasia in Artibeus lituratus (Chiroptera: Phyllostomidae) - Amaral Kuzel, Maria Alice (2023)
Artibeus lituratus (great fruit-eating bat; Phyllostomidae, Stenodermatinae) is a bat predominantly frugivorous species, with an important role in seed dispersal. The scarce literature on the morphology and pathology of bats is a challenge for professionals who study the species. This report presents the case of a free-living adult male of A. lituratus, captured during ecology and health studies in an Atlantic Forest remnant in the city of Rio de Janeiro, Brazil. The macroscopic examination of the structures showed a prostate, with about 0.5 cm in diameter, attached to the base of the urinary bladder, embracing part of the initial portion of the urethra and being composed of two well-defined regions: dorsal region and ventral region (involving the ventral part of the urethra) with the presence of homogeneous and whitish parenchyma. The urinary bladder was quite rigid and very thick with a lot of a whitish, friable and caseous material inside. On microscopic examination, this material was strongly eosinophilic and densely marked by PAS staining with the presence of sperm. The histology of prostatic region was preserved; however, the marked ectasia of the prostatic urethra was observed, with a large amount of refluxed material in its interior and flattening of the lining epithelium in part of the sample. This is the first report of this pathological process in A. lituratus and important to draw attention of veterinarians and other professionals about the presence of this pathology in bats.